A STUDY OF IDIOMS USED IN MISS PEREGRINE’S HOME FOR PECULIAR CHILDREN NOVEL - Siti Nufaisya; M. Syarfi M. Syarfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study is about the use of idiom in a novel entitled Miss Peregrine’s Home For Peculiar Children.The aim of this study is to find out whether or not idioms are found in the novel, the type of idiom based on McCarthy and O’Dell‟s theory (2010), and the meanings of idioms found in Miss Peregrine’s Home for Peculiar Children by Ransom Riggs. The object of the study was the English idiom in the novel Miss Peregrine’s Home for Peculiar Children by Ransom Riggs. The data were the phrases or words found in the novel. The data was collected in a particular way called a data collection method. The researcher collected the data by utilizing purposive sampling or judgment sampling. The theory that the researcher used for the data analysis is by Creswell (2009) and the categorizations using McCarthy and O'Dell (2010) theory. First, the data were identified to prove whether or not there were idioms. Second, the data were classified based on the types of idiom by McCarthy and O'Dell (2010). Third, the data were counted to get the percentage of each type of idioms. Then, the data were analyzed to understand the meaning of the collected data. Based on data analysis, there were found 63 idioms in the novel. Based on the analysis of the sentence in the novel, from 63 were classified into 7 types of idiom offered by McCarthy and O’Dell used. The researcher found there were 32 data of simile with 50,7% percentage, 7 data of cliché with 11,1% percentage, 10 data of fixed statement with 15,8% percentage, 4 data of euphemism 6,3% percentage, 6 Data of binomial with 9,5% percentage, 1 data of trinomial with 1,6% percentage, and 3 data of other languages with 4,7% percentage.Key Words: Idiom, Novel